Social Security as a Human Right Drafting a General Comment on Article 9 ICESCR - Some Challenges - Riedel, Eibe H. (Veröffentlichungen des Instituts für Deutsches, Europäisches und Internationales Medizinrecht, Gesundheitsrecht und Bioethik der Universitäten Heidelberg und Mannheim,, 2007)
Article 9 of the International Covenant on Economic Social and Cultural Rights on the right to social security is the shortest article in the entire Covenant and for that reason alone highly abstract and vague. A comprehensive analysis of the article 9 is still lacking, not least because it is widely regarded as a Pandora's box better not to be opened. Experience has shown that the quality of the state reporting procedure is greatly improved once the Committee on Economic Social and Cultural Rights has adopted a General Comment. Thus, it seems very desirable to close this gap. For the reason, an International Expert Workshop on the Right to Social Security was held in April 2005 at the German Institute for Human Rights, whose purpose was to highlight specific issues of the right to social security which should be addressed by the Committee when drafting a General Comment on article 9. The results of this workshop are published in this volume providing an insight into the current challenges on social security as a human right.